ANALISIS KUALITAS PELAYANAN INFORMASI PUBLIK PADA DINAS KOMINFOTIK KOTA BIMA - Dewi Yuli Yuliana; Wulandari Wulandari (Journal MISSY (Management and Business Strategy), 2023)
This study aims to analyze the quality of public information services at the informatics and statistical communication service (diskominfotik) Kota bima. This type of research is quantitative quantitative using descriptive method. As for the population in this study, namely the Bima City community, there were 96 samples with the sampling. Technique used, the results of this study indicate that the hypothesis used in the quality of public information services at the informatics and statistics communication service (diskominfotik) in Bima city is accepted and proven.